Effects of conjugation length and donor-acceptor functionalization on the non-linear optical properties of organic push-pull molecules using density functional theory - Datta, Anindya; Pal, S. (Journal of Molecular Structure-Theochem, 2005)
We consider a series of dipolar organic molecules where the donor groups and the acceptor groups are separated by pi-conjugation like phenyl ring or alkene chains. We have performed extensive quantum chemical calculations based on density functional theory (DFT) to calculate their linear and non-linear optical coefficients. We show that though DFT is known to overestimate the polarizabilities of quasilinear systems,the results with proper inclusion of exchange correlation compare well with the experimental studies. On increasing the pi-conjugation length, the coefficients increase non-linearly. We also vary the donor and the acceptor groups and study the role of chemical modifications on the response properties. Herein we suggest experimental methods by which the molecules may be arranged in non-centrosymmetric fashion in the bulk for device integration. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: DFr; donor-acceptor functionalization; non-linear properties; push-pull molecules